Examining the impact of factors that influence Universiti Utara Malaysia students' intention to enroll in Master of Business Administration - Darwina, Ab. Rahman (2015)
Development in business and administration area continues to get much attention from the government, higher educational institutions, and larger organizations. Higher educational institutions in Malaysia either private or public continue to offer Master of Business Administration program in order to produce a quality human resource in the field. This is based on the marketable of this program, high demand and job diversity associated with Business Administration. This study aims to examine the student’s intention to enroll in Master of Business Administration (MBA) program offered by Universiti Utara Malaysia (UUM). A survey involved students who enrolled in Bachelor of Business Administration with Honours (BBAHons) and 302 respondents was carried out. In addition, there are six main factors include personal factor, parental support, financial aids, job opportunities, quality of program and cost were used to help the researcher to find is there a relationship between selected factors that influence students’ intention to enroll in MBA program. A structured question was designed where the data were analyzed by SMARTPLS program to examine the relationship between selected factors and intention to enroll in MBA program. Results showed that personal factors, parental support, financial aids and job opportunities are significantly important determinants to predict student’s intention to enroll in MBA program whereas quality of program and cost are not significantly important determinants to predict student’s intention to enroll in MBA program